Copper, Chromium and Manganese in Water and Sediment of Kali Estuary, Karwar - M.P., Veer; H., Shanmukhappa; U.G., Bhat (Fishery Technology, 2025)
Copper, chromium and manganese concentrations ln the water and sediment samples along with some physicochemical parameters were determined at four stations of Kali estuary. The mean concentrations of Cu, Cr and Mn in water were 0.11, 0.044 and 0.327 ppm respectively. The corresponding values for sediment were 7.022, 14.13 and 185.66 ppm on dry weight basis. ln the spatial sequence, the variation in trace metals concentration of sediment exhibited a clear increasing trend from the estuarine mouth towards upstream. Range in temperature, salinity and dissolved oxygen were 27.30 - 34.00Â°C, 0.14 - 29.04% and 3.88 - 6.70 ml/1 respectively.